The history of co-operation in England : its literature and its advocates - Holyoake, George Jacob (1817-1906)
Le 2e volume porte en plus ce titre : "The Evolution of industry", et cette mention : "3d edition". - Index I. The pioneer period, 1812 to 1844 ; II. The constructive period, 1845 to 1878